KESIAPAN INFRASTRUKTUR PENDIDIKAN KOTA SAMARINDA MENJADI DAERAH PENYANGGA (HINTERLAND) KALIMANTAN TIMUR SEBAGAI CALON IBUKOTA NEGARA: READINESS OF EDUCATION INFRASTRUCTURE IN THE CITY OF SAMARINDA TO BECOME A SUPPORT AREA (HINTERLAND) EAST KALIMANTAN AS A PROSPECTIVE CAPITAL OF THE STATE - Bambang Supriyanto bambang; Fitri Nurmahmuda; Annisa Qomariah (SISTEMA: Jurnal Pendidikan, 2022)
Readiness of Samarinda City as a buffer area (hinter land) of East Kalimantan Province in terms of Education Infrastructure in welcoming the National Capital in 2024. This study uses a qualitative confirmatory approach. This research departs from an established and formal theory as a basis for making decisions. Data collection techniques, namely interviews and documentation. This study specifically discusses regional strengthening, especially the city of Samarinda as a buffer for the candidate for the state capital in East Kalimantan, this study is very important because the existence of the State Capital must receive support from the surrounding buffer areas, in terms of Currently, the cities that serve as other buffer zones are the City of Sepaku, North Penajam Paser Regency and Kutai Kartanegara Regency, Balikpapan City and Tanah Grogot City, Paser Regency. To strengthen the existence of buffer zones, especially the city of Samarinda, of course there must be a strategy that is applied, namely strengthening of capability and capacity (capacity building) which is carried out through the development of educational infrastructure, economic infrastructure, defense and security, politics, social, culture and local wisdom that applies throughout the country. East Kalimantan. From the description above, the big role of the buffer zone/hinter land can be described as follows: (1) Center for economic growth (2) Center for defense and security (3) Center for settlements (4) Center for food security (5) Center for education (6) Center for Agriculture (7) Plantation center (8) Fishery center (9) Industry center (10) Trade center (11) Growth center for growing area (12) Transportation center (13) Health center (14) Hygiene center (15) Recreation center And others. At a macro level, that Samarinda City as a buffer area is actually not ready to make Samarinda as a buffer zone for the state capital and efforts are needed to welcome the state capital, especially Samarinda city as a hinter land area/buffer area so that it can really contribute to development in all fields, especially education. Keywords: Relocation of the State Capital (IKN), Education Infrastructure